Comparison of Serum Zinc and Iron Levels Among Pregnant Women of Rural and Urban Areas Visiting Tertiary Care Hospital Jamshoro: Serum Zinc and Iron Levels in Pregnant Women - Ansari, Shabnam; Akbar, Sadia; Mumtaz, Nazia; Chang, Abid Hussain; Aamir, Kiran; Ujjan, Ikram din (Pakistan Journal of Health Sciences, 2024)
Nearly two-thirds of pregnant women in underdeveloped nations suffer from anemia, which increases the risk of maternal illness and death as well as low birth weight for the baby. Objective: Hospitalized pregnant women from rural and urban locations were compared for iron and serum zinc levels in this study. Methods: Total 146 pregnant women were presented in this Comparative Cross sectional study. This study was conducted in Department of Pathology, Laboratory, Liaquat University of Medical and Health Sciences, Jamshoro, Hyderabad. A red tip simple tube and Ethylenediaminetetraacetic acid (EDTA) were used to disperse 10 milliliters of blood sample. Cobas 601 was used for the analysis of serum iron. Micro Lab 300 was used for the analysis of zinc and copper. Results: There were 66 (45.2%) females had age 21-25 years, followed by 32 (22%) cases had age 26-30 years, 28 (19.1%) cases had age 17-20 years and 20 (13.7%) cases had age >30 years. There were 96 (65.8%) cases had history of consuming iron folic acid. There were 67 (45.9%) cases had good meal intake per day. Anemia was found in 103 (75.5%) cases. It was found that deficiency of serum zinc in 86 (58.9%) cases. Frequency of serum ferritin level was severe low in 44 (42.7%) cases, 49 (47.5%) cases had low serum ferritin level and normal ferritin level was only observed in 10 (9.8%) cases. Conclusions: it was found that pregnant women have increased anemia rates. Rural pregnant women are more likely than metropolitan ones to have this condition.